Reduced schedules of 4CMenB vaccine in infants and catch-up series in children: Immunogenicity and safety results from a randomised open-label phase 3b trial. Issue 28 (16th June 2017) - Martinón-Torres, Federico; Safadi, Marco Aurelio P.; Martinez, Alfonso Carmona; Marquez, Pilar Infante; Torres, Juan Carlos Tejedor; Weckx, Lily Yin; Moreira, Edson Duarte; Mensi, Ilhem; Calabresi, Marco; Toneatto, Daniela
Highlights: Reduced 2 + 1 dose schedules of 4CMenB in infants were assessed. Two catch-up doses of 4CMenB were administered 2 months apart in children 2–10 years. ≥88% of vaccinated infants achieved seroprotective antibody levels for 4CMenB components. ≥95% of children achieved seroprotective antibody levels for 4CMenB components. No safety signals were identified during the study. Abstract: Background: This study evaluated the immunogenicity and safety of a licensed meningococcal serogroup B vaccine (4CMenB) administered alone according to reduced schedules in infants or catch-up series in children. Methods: In this open-label, multicentre, phase 3b study (NCT01339923), infants randomised 1:1:1 received 4CMenB: 2 + 1 doses at 3½–5–11 months or 6–8–11 months of age, 3 + 1 doses at ages 2½–3½–5–11 months. Children aged 2–10 years received 2 catch-up doses administered 2 months apart. Immune responses were measured by hSBA assays against 4 strains specific for vaccine components fHbp, NadA, PorA and NHBA. Sufficiency of immune responses was defined in groups with 2 + 1 doses schedules as a lower limit ≥70% for the 97.5% confidence interval of the percentage of infants with hSBA titres ≥4, 1 month post-dose 2 for fHbp, NadA, PorA. Adverse events were collected for 7 days post-vaccination; serious adverse events (SAEs) throughout the study. Results: 754 infants and 404 children were enrolled. Post-primary vaccination, 98–100% of infants across all groups developed hSBA titres ≥4 for fHbp, NadA, PorA, and 48–77% for NHBA. Sufficiency of immune responses in infants receiving 2 + 1 schedules was demonstrated for fHbp, NadA, PorA after 2 doses of 4CMenB, as pre-specified criteria were met. Following receipt of 2 catch-up doses, 95–99% of children developed hSBA titres ≥4 for 4CMenB components. Similar safety profiles were observed across groups. A total of 45 SAEs were reported, 3 of which were related to vaccination. Conclusion: Reduced infant schedules and catch-up series in children were immunogenic and safe, having the potential to widen 4CMenB vaccine coverage. Funding: GlaxoSmithKline Biologicals SA.